Reliability of modified functional reach test in the assessment of balance function in people with spinal cord injury: a systematic review - Aatik Arsh; Haider Darain; Mujeeb Ur Rahman; Irfan Ullah; Syed Shakil-Ur-Rehman (Journal of the Pakistan Medical Association, 2021)
Objective: To systematically review the research studies that reported reliability of modified functional reach test for the assessment of sitting balance function in people with spinal cord injury. Methods: A systematic review was conducted according to PRISMA guidelines. Research studies published in English language from the earliest record to October 2019 that reported any type of reliability of modified functional reach test in assessing balance function in adult SCI population were included. Those studies were excluded which reported correlation of modified functional reach test with other outcome measures and not explicitly reported reliability of the modified functional reach test. Reviews, commentaries, letter to editors, conference papers and short communications were also excluded. Results: Initially, 108 research articles were retrieved from different databases, however after duplicate removal and applying inclusion/exclusion criteria, only 6 research studies were included in current systematic review. All 6 studies reported only test-retest reliability of modified functional reach test. Four studies measured only forward reach while remaining 2 studies measured reach in different directions. All 6 studies reported good to excellent reliability of modified functional reach test with interclass coefficient values ranging from 0.78 to 0.99. Conclusion: Modified functional reach test is a reliable tool for assessing sitting balance function in individuals with SCI. Continuous...